The Relationship Between Students' Critical Thinking Skills in Mathematics Learning Reviewed from Reflective and Impulsive Cognitive Styles - Nurun Ni'mah; M. Fatchurahman; Bulkani Bulkani; Agung Riadin (Suluh: Jurnal Bimbingan dan Konseling, 2025)
This study aims to determine the relationship and differences in critical thinking skills between students with reflective and impulsive cognitive styles in learning mathematics in college. Critical thinking skills are an important competency needed to understand and solve complex mathematical problems. Cognitive style, which reflects an individual's preferences in processing information, can affect the way students learn and think critically. The population of this study was 147 students consisting of all students of the 2023 intake who took Mathematics courses, but the sample taken was 64 students. The research instrument used a critical thinking skills test and a cognitive style test. The critical thinking skills test is in the form of mathematical questions that require in-depth analysis and evaluation, while the cognitive style test can use instruments such as the Matching Familiar Figures Test (MFFT) to group students into reflective and impulsive cognitive styles. Analysis of the quantitative data obtained will be analyzed using descriptive and inferential statistics. Statistical analysis can include correlation tests to see the relationship between cognitive style and critical thinking skills, as well as difference tests to compare critical thinking skills between groups of students with impulsive and reflective cognitive styles. The results of the study showed that there was a significant relationship (<0.05) between critical thinking skills and students' cognitive styles in learning mathematics. And there was a significant difference in critical thinking skills between students with impulsive cognitive styles and students with reflective cognitive styles. The differences were in the speed and accuracy of problem solving, evaluation and decision-making skills, and understanding of mathematical concepts.